Propuesta de modelo de un Sistema de Gestión de Seguridad y Salud en el Trabajo basado en la norma ISO 45001:2018 para la constructora PLADECO S.A. - Merino Jima, Jonathan Javier (2025)
This final work presents the design of an integrated occupational health and safety management system oriented to PLADECO S.A. The primary objective of this work is to develop a regulatory model specifically tailored to the company's needs, reinforcing its preventive culture and enhancing risk control in its unpredictable construction environment. The proposal is based on the regulatory framework of the ISO 45001:2018 standard and responds to internal requirements. The data collection process used a mixed approach, including semi-structured interviews with technical supervisors, surveys administered to operational personnel, and verification through direct observation and review of internal documents. The GTC 45 matrix identified, classified, and evaluated risks present in the workflow. The preliminary diagnosis exposed weaknesses in daily hazard control, poor record integration, and limited worker participation in preventive initiatives. However, the survey showed that the team welcomes the proposed changes. The diagnosis indicates that PLADECO S.A. has implemented an occupational health and safety management system in accordance with the ISO 45001:2018 standard. This system is positioned to enhance risk management and foster a proactive safety culture within the company.